Sistem Pendukung Keputusan Kelompok Pemilihan e-commerce/marketplace menggunakan metode profile matching dan BORDA - Pratistha, Indra; Agung Mahadewa, I Putu; Sugiartawan, Putu (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2018)
The increasing development of information technology, brings developments to the pattern of life of the Indonesian people, especially the pattern of consumption and shipping of goods. Indonesian society is greatly facilitated and spoiled in getting the desired goods and services. This development was caused by the spread of online shopping providers in Indonesia, which can be accessed via smartphones and computers. Indonesia has a very high number of smartphone users, judging from the number of unique audiences at the end of the second quarter, the data obtained from MMX Multi-platform, June 2017. One of the models used in this study is the Profile Matching method, the method can overcome problems ranking by giving weights based on matching two profiles examined on the criteria of each cell phone. The criteria obtained by the user will be the profile value which is then matched with the conformity profile provided by DM. This study uses three decision makers, including economists, IT experts, and the public. To combine the three decisions used the BORDA method approach. The BORDA method is a voting method that can resolve group decision making, wherein its application each decision maker (DM) provides a rating based on the alternative choices available. Furthermore, this research will use the approach of profile matching and BORDA methods in choosing the best marketplace. The results showed that Sophie's marketplace was ranked first.